Strategi Kelembagaan Pengelolaan Sampah Berbasis Masyarakat di Kecamatan Colomadu, Kabupaten Karanganyar - Rima Novira Sasmita; Jawoto Sih Setyono (Jurusan Perencanaan Wilayah dan Kota, 2016)
Solid waste problem happens almost in all cities in Indonesia, ranging from big cities to the small cities like Colomadu urban area. Colomadu itself has unique characteristic due to its exclave position fom Karanganyar Regency. As an exclave area, Colomadu is separated geographically from but is still part of Karanganyar administrative region. This position affects Colomadu because it is not covered by the solid waste management services from the respective regency institution (Dinas Kebersihan dan Pertamanan). As the consequences, about 70 per cent communities in Colomadu manage their solid waste with dumping and burning. This study aims to formulate institutional strategy of solid waste management in Colomadu district. There are two methods used in this research, i.e. research and planning methods. Observation and questionnaire data collection are used to understand recent solid waste management practices. The planning method is applied to comprehend stakeholder opinion about the concept of solid waste management. The research shows that the function of waste management institutions is not optimal yet. Therefore, waste management strategies which combine function and actors of institutions are needed. The key element of the strategies is the integration of multi-stakeholder to make a better and independent solid waste management in Colomadu.